Preconcentration of Trace Amounts of Pb(II) Ions without Any Chelating Agent by Using Magnetic Iron Oxide Nanoparticles prior to ETAAS Determination - S. Z. Mohammadi; T. Shamspur; M. A. Karimi; E. Naroui (The Scientific World Journal)
This work investigates the potential of magnetic Fe3O4 nanoparticles as an adsorbent for separation and preconcentration of trace amounts of lead from water samples prior to electrothermal atomic absorption spectrometry (ETAAS) determination. No chemical modifier is required in graphite furnace. Pb(II) ion was adsorbed on magnetic Fe3O4 nanoparticles in the pH range of 5.5–6.5, and then magnetic nanoparticles (MNPs) were easily separated from the aqueous solution by applying an external magnetic field; so, no filtration or centrifugation was necessary. After extraction and collection of MNPs, the analyte ions were eluted using HNO3 1.0 mol L−1. Several factors that may affect the preconcentration and extraction process, such as pH, type, and volume of eluent, amount of MNPs, sample volume, salting out effect, and interference ions were studied and optimized. Under the best experimental conditions, linearity was maintained between 0.005–0.5 ng mL−1. Detection limits for lead were 0.8 ng L−1 based on 3Sb. The relative standard deviation of seven replicate measurements of 0.05 ng mL−1 of Pb(II) ions was 3.8%. Finally, the method was successfully applied to extraction and determination of lead ions in the water and standard samples.